Pemanfaatan Media Video Pembelajaran untuk Meningkatkan Hasil Belajar pada Materi Pembangkit Listrik Tenaga Surya (PLTS) - Nur Rohima Oktiana; Rollis Kurnia Turangga; Adam Falrain Wibowo; Anas Nurfirdaus; Faqih Nazrul Hakim; Didik Aribowo (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
The rapid advancement of digital technology has driven a wide range of breakthroughs in the field of education, one of which is the growing use of video as an instructional medium in teaching and learning activities. This study departs from the actual conditions in the field where learning activities on the topic of Solar Power Plants (PLTS) are still frequently conducted in a conventional manner, relying heavily on lecture-based methods and text-based teaching materials, causing students to often struggle in comprehending the technical and mechanistic workings of the PLTS system in a comprehensive way. Based on this problem, this study aims to examine the extent to which the use of instructional video media is capable of driving improvements in student learning outcomes on the PLTS topic in the Electrical Engineering Vocational Education Study Program. The approach used in this study is Research and Development (R&D) with the ADDIE development model encompassing five stages, namely analysis, design, development, implementation, and evaluation. A One Group Pre-test Post-test Design was applied as the experimental framework to measure changes in student learning outcomes before and after the treatment using instructional video media. Data were collected through expert validation sheets, student response questionnaires, and cognitive test instruments in the form of pretest and posttest questions. All data obtained were then analyzed using a quantitative descriptive approach, with a paired sample t-test to examine differences in learning outcomes statistically. The findings of the study reveal that the use of instructional video media has demonstrably succeeded in improving student learning outcomes, with the most significant gains occurring in the domains of conceptual understanding and application. In addition, instructional video has also been shown to have a positive impact on student motivation and learning engagement, as evidenced by the high percentage of positive responses on the indicator of content relevance to real life. This study affirms that instructional video developed systematically and integrated appropriately into a broader pedagogical strategy holds strong support for improving the quality of vocational learning in the digital era.